Clock-controlled generators with large period output sequences. (1st January 2014) - Lin, Zhiqiang
Clock-controlled generators are a kind of pseudo-random number generators (PRNG). Recently, some clock-controlled generators based on jumping Linear Finite State Machines (LFSMs) have been proposed, such as Pomaranch and MICKEY . The period and the linear complexity of their output sequences need to be large enough to provide security against linear attacks. In this paper, a new condition for the period to reach its maximal value is presented. The condition is better than the previous one. Further, some clock-controlled generators are considered, including a new generator which uses a Feedback with Carry Shift Register (FCSR) as the control register. How to maximise the period of their output sequences is investigated.